Resources and Workforce in Top-Tier Psychiatric Hospitals in China: A Nationwide Survey - Xia, Lei; Jiang, Feng; Rakofsky, Jeffrey; Zhang, Yulong; Shi, Yudong; Zhang, Kai; Liu, Tingfang; Liu, Yuanli; Liu, Huanzhong; Tang, Yi-lang (Frontiers in Psychiatry, 2021)
Objectives: Mental healthcare has gained momentum and significant attention in China over the past three decades. However, many challenges still exist. This survey aimed to investigate mental health resources and the psychiatric workforce in representative top-tier psychiatric hospitals in China. Methods: A total of 41 top-tier psychiatric hospitals from 29 provinces participated, providing data about numbers and types of psychiatric beds, numbers of mental health professionals, outpatient services and hospitalization information covering the past 3 years, as well as teaching and training program affiliation. Results: Significant variations were found among participating hospitals and across different regions. Most of these hospitals were large, with a median number of psychiatric beds of 660 (range, 169-2,141). Child and geriatric beds accounted for 3.3% and 12.6% of all beds, respectively, and many hospitals had no specialized child or geriatric units. The overall ratios of psychiatrists, psychiatric nurses, and psychologists per bed were 0.16, 0.34, and 0.03, respectively. More than 40% of the hospitals had no clinical social workers. Based on the government’s staffing guidelines, less than one third (31.7%) of the hospitals reached the lower limit of the psychiatric staff per bed ratio, and 43.9% of them reached the lower limit of the nurse per bed ratio. Conclusion: Although some progress has been made, the shortage in psychiatric beds and in the workforce is still significant, especially regarding beds for children and elderly patients. In the meantime, the staffing composition needs to be optimized and more psychologists and social workers are needed. While addressing these shortages of mental health resources and the workforce is important, diversifying the psychiatric workforce, promoting community mental health care, and decentralizing mental health services may be equally important.